Overview of medically important antifungal azole derivatives. - Fromtling, R A (1988)
Fungal infections are a major burden to the health and welfare of modern humans. They range from simply cosmetic, non-life-threatening skin infections to severe, systemic infections that may lead to significant debilitation or death. The selection of chemotherapeutic agents useful for the treatment of fungal infections is small. In this overview, a major chemical group with antifungal activity, the azole derivatives, is examined. Included are historical and state of the art information on the in vitro activity, experimental in vivo activity, mode of action, pharmacokinetics, clinical studies, and uses and adverse reactions of imidazoles currently marketed (clotrimazole, miconazole, econazole, ketoconazole, bifonazole, butoconazole, croconazole, fenticonazole, isoconazole, oxiconazole, sulconazole, and tioconazole) and under development (aliconazole and omoconazole), as well as triazoles currently marketed (terconazole) and under development (fluconazole, itraconazole, vibunazole, alteconazole, and ICI 195,739).